Unlocking the Link: Sleep Deprivation and Cognitive Performance in Working-age Women - A Systematic Review - Jabade, Mangesh; Nadaf, Husain; Kaur, Jasneet; Singh, Shivcharan; Deshmukh, Jaya (Unnes Journal of Public Health, 2025)
Background: Sleep deprivation is a prevalent issue among working women, often resulting from a combination of professional, familial, as well as societal demands. Objective: This systematic review aims to summarize the body of research on the effects of sleep deprivation on cognitive function, focusing on working women in particular. Method: A comprehensive search was conducted across several databases to locate pertinent studies released between January 2014 and January 2024. Research has examined the relationship between sleep deprivation and executive function, memory, attention, and decision-making, among other cognitive abilities. The chosen studies' methodological quality was assessed, and relevant data were located and compiled. Results: The results indicate that sleep deprivation has a major negative impact on working women's cognitive function, with deficiencies noted in a number of domains. Age, workload, and family obligations may also increase these effects. Conclusion: To develop targeted therapies that can lessen the detrimental impacts of sleep deprivation and improve the wellbeing of women in the profession, a thorough understanding of how sleep deprivation affects cognitive performance is crucial.